Penerapan Kebijakan Digitalisasi Pelayanan Publik Pada Aplikasi BPOM Mobile - Nakhla Naqiyya Qonita; Muhammad Luthfi Rokhish; Muhammad Naufal Faruq (UIN Sunan Gunung Djati Bandung, 2024)
E-Government or Electronic Government is the use of information and communication technology (ICT) to provide public services and improve government efficiency and transparency. This article discusses one of the agencies that implement the E-Government system, namely the BPOM (Food and Drug Monitoring Agency). BPOM implements the E- Government system by issuing an application called BPOM Mobile. The purpose of the BPOM Mobile application is to make it easier for the public to ascertain whether the medicines and food sold around the community are registered or not. Therefore, the author conducted this research with the aim of finding data on whether the community has been helped in the E-Government process at BPOM. The research method in this paper uses the sentiment analysis method which is used to find data on the assessment of the community regarding the BPOM Mobile application by scraping data from the Google Play Store application. From the results of this analysis, it can be concluded that the community assesses that the BPOM Mobile application is still not effective in providing E-Government- based services. Therefore, the authors provide suggestions for the BPOM Mobile application to make it even better in the process of E-Government services to the public, the suggestions given involve making a website that is more accessible and easy to create, update, and maintain.